Coastal Conservation in Fishing Communities of Malang: Transforming Qur'anic Ecological Values through a Cultural Anthropology Perspective - Anam, Khoirul; Nasrulloh, Nasrulloh; Kadir, Abdul; Istiqomah, Nurul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Coastal regions hold strategic importance, particularly for fishing communities, due to their ecological, economic, and socio-cultural significance. In the coastal areas of Malang, these zones serve as the foundation of local livelihoods. However, unsustainable exploitation, environmental degradation, coastal abrasion, and the impacts of climate change have severely threatened the ecological sustainability of these areas. This study aims to examine the transformation of Qur’anic ecological values and the cultural anthropology of Malang's coastal communities in efforts to conserve the coastal environment. Employing a qualitative ethnographic method and an interdisciplinary framework that incorporates ecology, cultural anthropology, and interpretations of relevant Qur’anic verses, the research gathers data through in-depth interviews with community leaders, fishermen, religious figures, and textual analysis. The findings indicate that environmental conservation can be more effectively pursued through an integrated approach that merges Qur’anic principles, ecological awareness, and anthropological insights. Qur’anic ecological concepts—such as khilāfah (stewardship), tawāzun (balance), and fasād (corruption or degradation)—foster a heightened awareness of human responsibility toward environmental stewardship. Simultaneously, from an anthropological perspective, human-environment relationships are expressed through symbolic acts of reverence, such as sea and earth offerings. Thus, the integration of Qur’anic and anthropological values offers a comprehensive and culturally resonant framework for ecological preservation, contributing to sustainable community development.